1998
DOI: 10.1088/0026-1394/35/4/55
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric applications of Fourier-transform spectrometers

Abstract: Filter radiometers are used as transfer standards in many radiometric measurements, and essentially comprise a detector, filter (interference or coloured glass) and high-precision aperture. An initial study into the use of Fourier-transform (FT) spectrometry has resulted in the attainment of medium accuracy (around 0.3 % to 0.7 %) calibration of assembled filter radiometers in a period of a few hours. This contrasts with a day for characterization using a grating instrument and the weeks required for high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The first has been checked by determining the transmission profile (the main variable) of the double AOTF system using an FT spectrometer as a convenient measurement tool. A description of this FT spectrometer and its use for radiometric measurements is described elsewhere in these proceedings [19]. These measurements showed that the transmission profile of the AOTF system could be effectively modelled to an uncertainty of less than 0.5 % (1 ) in terms of its integrated spectral transmittance as a function of RF frequency and power.…”
Section: Absolute Spectroradiometersmentioning
confidence: 99%
“…The first has been checked by determining the transmission profile (the main variable) of the double AOTF system using an FT spectrometer as a convenient measurement tool. A description of this FT spectrometer and its use for radiometric measurements is described elsewhere in these proceedings [19]. These measurements showed that the transmission profile of the AOTF system could be effectively modelled to an uncertainty of less than 0.5 % (1 ) in terms of its integrated spectral transmittance as a function of RF frequency and power.…”
Section: Absolute Spectroradiometersmentioning
confidence: 99%
“…If the excretion mechanism of uric acid in human body degenerates, it will lead to gout and other diseases. 8,9 Therefore, in recent years, multifarious and new sensors have been developed to detect these three substances, such as ionic chromatography, 10,11 high performance liquid chromatography, 12,13 calorimetry, 14 spectrophotometry, 15,16 electrochemical method, 1,[17][18][19][20] etc. Among them, electrochemical method has been widely developed because of its rapid sensitivity, high selectivity and excellent stability.…”
mentioning
confidence: 99%